KEANEKARAGAMAN JENIS SATWALIAR DI KAWASAN KEBUN KELAPA SAWIT DAN STATUS PERLINDUNGANNYA (Studi Kasus: Perkebunan Kelapa Sawit PT. Sawit Sukses Sejahtera Kabupaten Kutai Timur-Provinsi Kalimantan Timur) - Harnios Arief; Yanuar Wicaksono (Media Konservasi, 2014)
Land cover in the area of PT Sawit Sukses Sejahtera before being converted into oil palm plantations around the year 2009 is generally open areas, shrub and degraded forest. Changes in land cover has been started since 1982 are due to the large fire in 1997 and then repeated the forest ecosystem degradation continued after the reform due to illegal logging and encroachment. Results of field observations indicate that the level of a wild life species richness is relatively low to very low and generally concentrate in areas with relatively good cover. These are as are generally secondary forest or plantation and the land is still owned by the general public. The concession area is an area containing wild life species richness is relatively low when compared to natural forest ecosystems. Then this area is also a habitat for the types of wild life that has been able to adapt to the conditions of this degraded. This region is habitat for 59 species of birds comprising 35 species belonging to 23 families, 16 species of mammals belonging to13 families and 8 species of reptiles belonging to 5 families. Then based on the results of data analysis with rare wild life/protected among the 59 species there that fall into the kind of rare/protected and included three local endangered due to habitat fragmentation and poaching.  Keywords: Ecosystem, Fragmentation, Land cover, Landscape and Species richness of wildlife.